Mandibular reconstruction with fibula free flap: case series - Marcel Fernando Miranda Batista Lima; Juan Pablo Borges Rodrigues Maricevich; Jairo Zacchê de Sá; Kelson Kawamura; Rafael Anlicoara (Revista Brasileira de Cirurgia Plástica, 2020)
Introduction: Mandibular reconstruction is a complex procedure aimed at correcting defects of the lower third of the face and achieving functional rehabilitation, including chewing and oral competence. Fibula free flap is the first choice for the reconstruction of segment defects of the adjacent mandible and soft tissue. Methods: A retrospective clinical study was conducted from January 2005 to July 2017, analyzing the medical records of patients undergoing microsurgical reconstructions after resection of head and neck neoplasms at the plastic surgery service of the Clinical Hospital of the Federal University of Pernambuco (HC-UFPE). Results: This study included six patients, of which three were men (50%), aged between 12 and 48 years and with a mean age of 24 years. In 83% of the cases, reconstructions were performed with osteomyocutaneous fibula free flaps (in one case, there was no need for skin island flap). We observed an adequate coverage of the large defects analyzed, with good functional and aesthetic appearance in all cases. Immediate reconstruction was performed in 83% of cases. The fibula and receptive area were prototyped in two cases. Conclusion: Fibula free flaps are a great alternative for head and neck reconstruction. Our initial experience and literature show satisfactory results, partially restoring the shape and function of the affected areas.